Gooney Bird and all her charms - Lowry, Lois (Lowry, Lois. Gooney Bird Greene., 2013)
Gooney Bird's Great Uncle Walter lends her second grade class a skeleton while they study human anatomy, and at the end of the month the students use Gooney Bird's charm bracelet to present all they have learned.